The Brain Is Not a Computer: David Gelernter & Critics. - MENDLOVIC, JACOB; FRENKEL, ROBERT; LUCENTINI, MAURO; FRANK, AARON; STEIN, STEVE; DAN, PETER; CARROLL, RONALD J.; BAILEY, MATTHEW; SIMON, M.; NOUR EDDINE, SAMER; BLAZ, JERRY; ELLWANGER, ADAM; et al. (Commentary, 2014)
The article presents several letters to the editor in response to the article "The Closing of the Scientific Mind" by David Gelernter published in the January 2014 issue.